KEBERHASILAN DUA JENIS STERILAN DAN LAMA PENYINARAN LAMPU UV (ULTRA VIOLET) PADA STERILISASI EKSPLAN BONGGOL PISANG TALAS (Musa paradisiaca L. var. sapientum) - Hemy Sriana; Raihani Wahdah; Hilda Susanti (Universitas Lambung Mangkurat, 2022)
The technique of cultivating talas bananas through tissue culture with corm explants can produce a large number of seedlings with uniform height and in a short time compared to conventional methods. However, it has a higher level of contamination, so it uses HgCl2 as the sterilant which is classified as hazardous and toxic (B3) chemical. The use of UV light exposure which is able to nonactivate contaminants can be recommended to replace the B3 material. The purposes of this study were to investigate the difference between the control and the UV light exposure time nested in sterilant types on the success of sterilization of talas banana (Musa paradisiaca L.var. Sapientum) corm explant; and to investigate the effects of sterilant types on the success of sterilization of talas banana (Musa paradisiaca L.var. Sapientum) corm explant. This study is an experimental study arranged in a Nested Completely Randomized Design with separate control repeated 3 times. The UV light exposure time (t1 = 1.0 hours; t2 = 1.5 hours; t3 = 2.0 hours; t4 = 2.5 hours and t5 = 3.0 hours) was nested in a type of sterilant (s1 = UV light; s2 = 0.2% Fungicide + 0.2% Bactericide + 70% Alcohol + 30% Bayclin + 20% Bayclin + Betadine + UV light). The results of the study show that the sterilization of talas banana corm explants (s1 type), without using B3 HgCl2 and only using UV light, can be recommended to be applied in the propagation of talas bananas through in vitro culture.